Assumption 1:

If A is lying ==>B should be telling the truth.

If B is correct then C must be lying.

C says "A & B both are lying".

It will be a lie as B is telling the truth.

So this works.

Assumption 2:

If B is lying==>C should be telling truth.

That means, A and B both must be lying.But this contradicts our assumption.

So it wont work

Assumption 3:

If C is lying==>A & B both are saying the truth.

But this will contradict the A's statement.

So it wont work.

Assumption 4:

If all are lying.

Then B should be telling the truth as per A.This is a contradiction.

Hence this also won't work.

Hence B must be telling the truth as per the assumption 1.

I guess this is the answer.

I go with PSM.